Antimicrobial nanofibrous mats with controllable drug release produced from hydrophobized hyaluronan - Bardoňová, Lenka; Kotzianová, Adéla; Skuhrovcová, Kristýna; Židek, Ondřej; Bártová, Tereza; Kulhánek, Jaromír; Hanová, Tereza; Mamulová Kutláková, Kateřina; Vágnerová, Hana; Krpatová, Věra; Knor, Michal; Starigazdová, Jana; et al. (Carbohydrate polymers, 2021)
Due to their large active surface, high loading efficiency, and tunable dissolution profiles, nanofibrous mats are often cited as promising drug carriers or antimicrobial membranes. Hyaluronic acid has outstanding biocompatibility, but it is hydrophilic. Nanofibrous structures made from hyaluronan dissolve immediately, making them unsuitable for controlled drug release and longer applications. We aimed to prepare a hyaluronan-based antimicrobial nanofibrous material, which would retain its integrity in aqueous environments. Self-supporting nanofibrous mats containing octenidine dihydrochloride or triclosan were produced by electrospinning from hydrophobized hyaluronan modified with a symmetric lauric acid anhydride. The nanofibrous mats required no cross-linking to be stable in PBS for 7 days. The encapsulation efficiency of antiseptics was nearly 100%. Minimal release of octenidine was observed, while up to 30% of triclosan was gradually released in 72 h. The nanofibrous materials exhibited antimicrobial activity, the fibroblast viability was directly dependent on the antiseptic content and its release.
Keywords: Animals; pyridiny; 3T3 Cells; iminy; mikrobiální testy citlivosti; nanovlákna; Imines; Drug Carriers; triclosan; Mice; Anti-Bacterial Agents; Nanofibers; kyselina hyaluronová; Drug Liberation; myši; Hyaluronic Acid; Staphylococcus aureus; Triclosan; Microbial Sensitivity Tests; léky s prodlouženým účinkem; Delayed-Action Preparations; Pseudomonas aeruginosa; Pyridines; buňky 3T3; nosiče léků; zvířata; uvolňování léčiv; antibakteriální látky; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions